Estudo morfofisiológico e anatômico de dois genótipos de cacaueiro (Theobroma cacao L.) submetidos a diferentes condições de radiação solar - Furlan, Larissa Maria (2013)
The luminosity emerges as one of the most important abiotic factors in the establishment of plants and can cause changes in physiological and anatomical, interfering directly in their development and consequently their productivity. The cocoa tree (Theobroma cacao - Malvaceae ) has great economic interest due to the use of its seeds to produce cocoa butter and chocolate. In this sense, the objective of this study was to compare physiological and anatomical characteristics of two genotypes of cacao (PH 16 and IPIRANGA 01), subject to different conditions of solar radiation in order to infer about the lighting conditions most favorable to their development. Analyses of growth, pigment content, gas exchange and anatomical stem and leaf. The experimental design was randomized blocks (DBC), with four replications in a factorial 2 x 5 , consisting of two genotypes and 5 brightness levels ( 0 % - full sun - 18 % , 30 % , 50 % and 80% shading), totaling 40 plots with 10 plants each. Data were subjected to analysis of variance and regression. The results indicate higher growth adaptation in both genotypes under conditions of moderate to high irradiance. The quality index Dickson demonstrated greater ability to survive under field conditions with high levels of irradiance for genotype PH 16 and moderate levels of irradiance for IPIRANGA 01. The content of photosynthetic pigments of IPIRANGA 01 show up higher in the condition of 30% shade, while for PH 16 the highest levels were observed in 50% shade . Both genotypes showed high rates of A, C , E, A / E , A / Gs and A / Ci, under high irradiance, as well as stem and leaf anatomical adaptations to higher luminosities, such as greater thickening of the leaf, parenchyma palisade and spongy, leaf blade, adaxial stomatal density, higher density, frequency of vessel elements and thickness of secondary xylem . Genotypes PH 16 and IPIRANGA 01 showed a large plasticity in relation to different levels of irradiance, however, it was found that PH 16 performed better under high irradiance, as obtained from treatments in full sun and 18% shade, while IPIRANGA 01 was more adapted under moderate shading, 30% shading.